If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(t + 2) + 5t = 6t + 11 Reorder the terms: -2(2 + t) + 5t = 6t + 11 (2 * -2 + t * -2) + 5t = 6t + 11 (-4 + -2t) + 5t = 6t + 11 Combine like terms: -2t + 5t = 3t -4 + 3t = 6t + 11 Reorder the terms: -4 + 3t = 11 + 6t Solving -4 + 3t = 11 + 6t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-6t' to each side of the equation. -4 + 3t + -6t = 11 + 6t + -6t Combine like terms: 3t + -6t = -3t -4 + -3t = 11 + 6t + -6t Combine like terms: 6t + -6t = 0 -4 + -3t = 11 + 0 -4 + -3t = 11 Add '4' to each side of the equation. -4 + 4 + -3t = 11 + 4 Combine like terms: -4 + 4 = 0 0 + -3t = 11 + 4 -3t = 11 + 4 Combine like terms: 11 + 4 = 15 -3t = 15 Divide each side by '-3'. t = -5 Simplifying t = -5
| 5s+17=157 | | 7h+4=7 | | 2.4=2+0.3x | | 7p^2+6=0 | | X-4x=231 | | 2cosx=x | | 4*(d-3)=2d | | 9x-2y=-18 | | 8x^3-28x+29=0 | | 93+12m=3(4m-1) | | W^2+w+56= | | 6cos^2x-7cosX-10=0 | | 13=10n+6 | | 15*m=5 | | x+ln((x^2)-4)=0 | | 2x^2+12x+50=0 | | 2-4=4(2)-10 | | 4+7f=4 | | 120x+320=30-(x-3) | | q*q=15+1 | | factorx^2+12x+2=0 | | 120x+320=0.3-(x-3) | | 100x+700=60(x-3) | | 10x+35=6-(x-3) | | p*p=1 | | 36+32=13-(x-3) | | 7r+2=5(r-4)whatisx | | 5x(3x+5)=10 | | w=21+2p | | 3.2x+14=-4 | | 163.2+23.84x-16x^2=4 | | 5x(3x+5)=5 |